1999
DOI: 10.1046/j.1440-1827.1999.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase IV (DPP IV/CD26) staining predicts distant metastasis of ‘benign’ thyroid tumor

Abstract: Because follicular thyroid carcinoma is extremely difficult to diagnose, several cases were encountered which have been rediagnosed as carcinoma due to distant metastasis. In the search for a method of correctly diagnosing 'benign' thyroid tumor, dipeptidyl peptidase (DPP) IV immunostaining was applied to 10 cases whose diagnoses had been corrected to follicular thyroid carcinoma because of distant metastases. The positive rate of immunostaining using paraffin sections in the rediagnosed follicular thyroid car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 3 publications
2
19
0
1
Order By: Relevance
“…Other studies also demonstrated the involvement of seprase and matrix metalloproteases in breast cancer cell invasion (32,33). A retrospective study on follicular thyroid carcinoma supports the proposal that DPPIV could be a marker for cell invasiveness (34). Here we show that the seprase-DPPIV complex is also a marker for connective tissue cell invasiveness and the invadopodia of migrating fibroblasts.…”
Section: Figsupporting
confidence: 85%
“…Other studies also demonstrated the involvement of seprase and matrix metalloproteases in breast cancer cell invasion (32,33). A retrospective study on follicular thyroid carcinoma supports the proposal that DPPIV could be a marker for cell invasiveness (34). Here we show that the seprase-DPPIV complex is also a marker for connective tissue cell invasiveness and the invadopodia of migrating fibroblasts.…”
Section: Figsupporting
confidence: 85%
“…On the contrary, inhibition of CD26 in renal cell carcinoma decreased tumor growth and reduced binding of the cancer cells to fibronectin and collagen (15). Moreover, clinical studies in thyroid cancer, GIST, and T-cell non-Hodgkin lymphoma/leukemias suggested that CD26 expression was associated with distant metastasis, recurrence after resection, or poor survival (16,18,44). The multifunctional roles of CD26 may account for its varied roles in different cancers (11).…”
Section: Discussionmentioning
confidence: 99%
“…33 It is expressed on a wide variety of cell lineages including T lymphocytes, endothelial and epithelial 34,35 Differential diagnosis of follicular carcinoma of the thyroid from follicular adenoma has been one of the most difficult tasks for surgical pathologists. CD26 is a 110-kDa cell membrane glycoprotein that belongs to the serine protease family (EC 3.4.14.5).…”
Section: Discussionmentioning
confidence: 99%